Torreffaction of empty fruit bunch in a fixed bed reactor / Wilson Tungku, Azrinawati Mohd Zin and Alina Rahayu Mohamed - Wilson, Tungku; Mohd Zin, Azrinawati; Mohamed, Alina Rahayu (2020)
The natural forest in Malaysia had produced a largest biomass resource due to the agricultures activities. Not only that, Malaysia also produces a lot of solid waste such as empty fruit bunch because Malaysia is the second top producer of palm oil. In this study, the empty fruit bunch (EFB) is used as the biomass because of its abundant resources. Biomass has a higher moisture content and lower calorific value than coal. In response to the issues related to environment pollution, renewable energy such as biomass has been recognized as a solution to overcome the problem related to the degradation of natural resources. In this study, torrefaction process has been introduced to increase the calorific value, lower the moisture content and also to produce a better fuel quality. Therefore, the purposes of this study are to study the effect of torrefaction temperature and holding time on the mass yield of torrefied EFB and to assess the activation energy, Ea of torrefaction process by using the Coats-Redfern method. The torrefaction of EFB was performed in a fixed-bed reactor under an inert environment. The effects of various torrefaction temperatures between 200 and 300 oC and holding times of 20, 40 and 60 minutes on the mass yield of EFB were investigated. The results showed that temperature significantly influenced the mass yield of EFB during torrefaction. It was determined that the mass yield decreased upon increasing torrefaction temperature. The highest activation energy values for EFB was 37.09 kJ/mol at holding time of 20 minutes, respectively. In this study, the torrefaction process can be proven that the torrofired biomass can improvise its characteristic of biomass.